Origins of sociology / by Albion W. Small. - Small, Albion W., 1854-1926. (Tufts University. Tisch Library., 2020)
1 online resource (vii, 359 pages); "First published serially in the American Journal of Sociology, January, 1923-November, 1924, with the title 'Some contributions to the history of sociology'"--Preface.; Tisch In-House Digitization 2020-01-27